Thermo-Economic Optimization of a Novel Supercritical CO₂ Brayton Cycle Integrated with Concentrated Solar Power for High-Efficiency Electricity (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The basic idea of this presented research is to modernize the electricity generation system with high quality and provide development in the economical and thermal mechanical design of the Bratton cycle. This research includes an advanced study of economic and analytical studies to give an ideal superior operational quality and enlarge the energy storage space while reducing excess costs. We used in this research the technology of simulating thermal movement in addition to the benefit of economic analysis to study variables on operational capabilities and benefit from them. The lower cycle also has an important role in thermal balance and modern experience has confirmed that it is more efficient than the old system in developing solar systems to reduce costs and consumption of thermal pressure inside. The system.